Soldaten op het Koningsplein. Uit: archief F. Domela Nieuwenhuis, VI a I B, no. 26. Originele foto: BG A61/163
Soldaten op het Koningsplein. Uit: archief F. Domela Nieuwenhuis, VI a I B, no. 26. Originele foto: BG A61/163.